2006
DOI: 10.1128/cmr.19.2.403-434.2006
|View full text |Cite
|
Sign up to set email alerts
|

Burn Wound Infections

Abstract: SUMMARYBurns are one of the most common and devastating forms of trauma. Patients with serious thermal injury require immediate specialized care in order to minimize morbidity and mortality. Significant thermal injuries induce a state of immunosuppression that predisposes burn patients to infectious complications. A current summary of the classifications of burn wound infections, including their diagnosis, treatment, and prevention, is given. Early excision of the eschar has substantially decreased the inciden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

25
1,410
4
60

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,623 publications
(1,499 citation statements)
references
References 428 publications
(692 reference statements)
25
1,410
4
60
Order By: Relevance
“…Colonisation of fungi in wounds is associated with the use of broadspectrum antibiotics [21]. In patients with cutaneous trauma, Fusarium spp.…”
Section: Fusarium Biofilmsmentioning
confidence: 99%
“…Colonisation of fungi in wounds is associated with the use of broadspectrum antibiotics [21]. In patients with cutaneous trauma, Fusarium spp.…”
Section: Fusarium Biofilmsmentioning
confidence: 99%
“…Infection of wound surfaces often causes delayed healing or nonhealing of the wound, which results in mortality [2]. It was reported that infection was responsible for 75% of all deaths in patients with burns exceeding 40% of the total body surface area [3].…”
Section: Introductionmentioning
confidence: 99%
“…Immediately following wounding, whether it is caused by a severe burn, trauma or surgery, the affected area is at risk of colonization by a variety of micro-organisms, which proliferate within the damaged tissues and establish an infection (Church et al, 2006;Kooistra-Smid et al, 2009;Posluszny et al, 2011;Rafla & Tredget, 2011). These microorganisms may come from the host's skin, respiratory or gastrointestinal flora (Church et al, 2006;Posluszny et al, 2011;Rafla & Tredget, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Damage to the skin and its underlying connective tissues breaches its innate physical and chemical protective mechanisms (Church et al, 2006;Posluszny et al, 2011). Immediately following wounding, whether it is caused by a severe burn, trauma or surgery, the affected area is at risk of colonization by a variety of micro-organisms, which proliferate within the damaged tissues and establish an infection (Church et al, 2006;Kooistra-Smid et al, 2009;Posluszny et al, 2011;Rafla & Tredget, 2011).…”
Section: Introductionmentioning
confidence: 99%